The standardization of method and time of propagation in guava (Psidium guajava) - RANI, SOHNIKA; SHARMA, AKASH; WALI, V K; BAKSHI, PARSHANT; AHMED, SHAHNAWAZ (The Indian Journal of Agricultural Sciences, 2015)
The present investigation on the standardization of method and time of propagation in guava (Psidium guajava L.) was experimented during four different months, viz. June, July, August and September with four different methods, i.e. cuttings, air layering, patch budding and wedge grafting during the year 2012-13. It was observed that among all propagation methods, patch budding performed during 15 to 21 August showed highest per cent success (92.07%) recorded after 90 days of propagation. After 180 days of guava propagation, maximum number of new shoots per plant (8.97), number of leaves/plant (22.39), scion thickness (1.34 cm) were recorded in wedge grafting performed during 15 to 21 September while, air layering during 15 to 21 August took minimum days to sprout (11.75) with maximum increase in plant height (61.89 cm).